Epigenetic Age Acceleration and Cognitive Function in African American Adults in Midlife: The Atherosclerosis Risk in Communities Study. (20th October 2019) - Bressler, Jan; Marioni, Riccardo E; Walker, Rosie M; Xia, Rui; Gottesman, Rebecca F; Windham, B Gwen; Grove, Megan L; Guan, Weihua; Pankow, James S; Evans, Kathryn L; Mcintosh, Andrew M; Deary, Ian J; et al.
Abstract: Methylation levels measured at defined sites across the genome have recently been shown to be correlated with an individual's chronological age. Age acceleration, or the difference between age estimated from DNA methylation status and chronological age, has been proposed as a novel biomarker of aging. In this study, the cross-sectional association between two different measures of age acceleration and cognitive function was investigated using whole blood samples from 2, 157 African American participants 47–70 years of age in the population-based Atherosclerosis Risk in Communities (ARIC) Study. Cognition was evaluated using three domain-specific tests. A significant inverse association between a 1-year increase in age acceleration calculated using a blood-based age predictor and scores on the Word Fluency Test was found using a general linear model adjusted for chronological age, gender, and years of education (β = −0.140 words; p = .001) and after adding other potential confounding variables (β = −0.104 words, p = .023). The results were replicated in 1, 670 European participants in the Generation Scotland: Scottish Family Health Study (fully adjusted model: β = −0.199 words; p = .034). A significant association was also identified in a trans-ethnic meta-analysis across cohorts that included an additional 708 European American ARIC study participants (fully adjusted model: β = −0.110 words, p = .003). There were no associations found using an estimate of age acceleration derived from multiple tissues. These findings provide evidence that age acceleration is a correlate of performance on a test of verbal fluency in middle-aged adults.